ON THE ISSUE OF PROFESSIONALISM IN POLITICAL JOURNALISM - A. Y. Kolianov (Дискурс)
The article actualizes the necessity to study professionalism in political journalism. The author analyzesstructural elements of the problem as well as possible scientific approaches to its solution.